Tubercular synovitis mimicking rheumatoid nodules - Teoh, Soo Chin; George, J.; Kamarul, Tunku (Malaysian Medical Association, 2008)
Tubercular tenosynovitis is an uncommon condition and usually affects the upper limb. We report a case of a patient with Systemic Lupus Erythematosus who presented with wrist swelling. The clinical findings were suggestive of rheumatoid nodules, but the radiographic finding of calcification associated with the nodules and marked erosive changes primarily of the radio-carpal joint with sparing of the metacarpal joints led the radiologist to believe that the nodules may not be rheumatoid nodules. The presence of solid and fluid nature of the nodule and hyperechoic small echogenic foci (matted rice bodies within thickened synovium) on ultrasound suggested the presence of chronic synovitis of tuberculous infection rather than rheumatoid nodule as in our case. We recommend the use of ultrasound to determine the nature of nodular swellings seen clinically in patients with arthropathy.